2008
DOI: 10.2337/dc07-1835
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of A1C to Glucose Concentrations in Children With Type 1 Diabetes

Abstract: Assessments by high-frequency glucose determinations by sensors DIABETES RESEARCH IN CHILDREN NETWORK (DIRECNET) STUDY GROUP*OBJECTIVE -Despite the standing of A1C as the most validated and widely used measure for average glycemic control over time, the relationship between A1C and glucose concentrations is not completely understood. The purpose of this Diabetes Research in Children Network (DirecNet) study was to use continuous glucose monitoring data to examine the relationship between A1C and glucose in typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(36 citation statements)
references
References 17 publications
2
33
1
Order By: Relevance
“…A recent study comparing A1C to CGM data in 48 type 1 diabetic children found a highly statistically significant correlation between A1C and mean blood glucose, although the correlation ( r = 0.7) was significantly lower than in the ADAG trial (51). Whether there are significant differences in how A1C relates to average glucose in children or in African American patients is an area for further study.…”
Section: Diabetes Carementioning
confidence: 80%
“…A recent study comparing A1C to CGM data in 48 type 1 diabetic children found a highly statistically significant correlation between A1C and mean blood glucose, although the correlation ( r = 0.7) was significantly lower than in the ADAG trial (51). Whether there are significant differences in how A1C relates to average glucose in children or in African American patients is an area for further study.…”
Section: Diabetes Carementioning
confidence: 80%
“…A small study comparing A1C to CGM data in type 1 children found a highly statistically significant correlation between A1C and mean blood glucose, although the correlation ( r = 0.7) was significantly lower than in the ADAG trial (69). Whether there are significant differences in how A1C relates to average glucose in children or in African American patients is an area for further study.…”
Section: Diabetes Carementioning
confidence: 84%
“…Controversy persists over the underlying assumption that A1C levels depend exclusively on long-term previous blood glucose concentration (26). A number of studies have shown that biological variation in A1C is influenced by factors other than blood glucose concentration (7–13). This suggests that eAG may be a systematically biased estimate of self-monitored mean blood glucose (MBG).…”
mentioning
confidence: 99%